Rancang Bangun Sistem Monitoring Ketinggian Air Sungai Piji Berbasis Internet Of Things menggunakan Cloudflare - Luthfi Wilda Haqiqi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Flooding is a frequent disaster in Kudus City, particularly in Kesambi Village, particularly around the Piji River, due to high rainfall and the lack of an effective early warning system. This research aims to design and build a website-based water level monitoring system for the Piji River, utilizing Internet of Things (IoT) technology and Cloudflare services.This system uses an ESP32 device connected to a water level sensor to read river water levels in real time. Sensor readings are sent to a web server over the internet using the HTTPS protocol, secured by Cloudflare. Cloudflare acts as a server intermediary through Cloudflare Tunnel, providing a layer of security without requiring a public IP address.Data received by the server is stored in a database and displayed on the website in tables and graphs, allowing users to access them anytime and anywhere. The results of this system design are expected to assist the public and relevant parties in effectively monitoring river water levels as an early mitigation measure against potential flooding.